Kedudukan Harta Gono-Gini dalam Pembagian Harta Waris Menurut Hukum Islam - Yuli Andini Puspitasari; Navyra Berlianny; Mila Sari; Putri Yanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Marriage is a universal rule that applies to all creatures, including humans, animals and plants, as a way to reproduce and maintain life. In Islam, marriage means a contract between a man and a woman's guardian which makes sexual relations halal. A marriage can end due to death, divorce, or court settlement. Divorce is seen as the final step if the relationship cannot be repaired, and in the Qur'an and Hadith, there are no detailed provisions regarding the divorce process, so the law can be adjusted to the situation. One of the consequences of marriage is the existence of, Common Property Treasure acquired during the marriage, and must be managed responsibly by husband and wife. This concept is regulated in Indonesian laws and regulations, such as the Marriage Law, Civil Code, and the Compilation of Islamic Law., Common Property Treasure includes wealth acquired during marriage and belongs jointly to husband and wife, while inherited property is wealth owned before marriage. The issue of, Common Property Treasure has not been widely discussed in classical jurisprudence studies, but in the modern context, this has become important to ensure justice in Division of assets in case of divorce. Islamic law allows the distribution of assets through deliberation or court decisions if necessary. The concept of community property supports the fair distribution of wealth between husband and wife, in accordance with the principles of justice in Islam.